Doping Effects in the Charge Transport of Graphene-Porphyrins - Cardenas-Jiron, G (American Chemical Society, 2016)
Doping effects of B, N, and phosphorus (PHP) in graphene and of aza N in porphyrin of graphene-porphyrin (GP) complexes bonded through an amide group have been studied using density functional theory (DFT) and time-dependent DFT mainly at the M06/6-31G(d,p) level of theory. Structural, optical, electronic, and charge transport properties are analyzed for a set of eight GP complexes. We found that all GP complexes feature the characteristic absorption bands of porphyrin in the visible region, Q and Soret, showing P → P electronic transitions. Charge transfer between the fragments graphene and porphyrin in both directions P → G and G → P is obtained in the excited states, but the absorptions are of lower intensity when compared to the P → P ones. Doping only the graphene group of GP yields blue-shifted porphyrin absorptions; however, doping graphene and porphyrin yields red-shifted absorptions. Doping leads to a reduction of the HOMO-LUMO gap in all GP complexes, because the dopant atoms perturbation of the electronic density favors the electronic transitions in the visible region. Depending on the dopant type and the direction of the bias voltage, introducing dopants can significantly affect the electrical conductance of graphene-porphyrin complexes. The results of this work show that porphyrin keeps its properties as photosensitizer when it is covalently bonded to graphene; therefore these complexes can be used as efficient harvesters of solar light. © 2016 American Chemical Society.